Regulation of the microvasculature during small muscle mass exercise in chronic obstructive pulmonary disease vs. chronic heart failure - Hartmann, Jacob Peter; Dahl, Rasmus H.; Nymand, Stine; Munch, Gregers W.; Ryrsø, Camilla K.; Pedersen, Bente K.; Thaning, Pia; Mortensen, Stefan P.; Berg, Ronan M. G.; Iepsen, Ulrik Winning (Frontiers in Physiology, 2022)
Abstract Aim: Skeletal muscle convective and diffusive oxygen (O2) transport are peripheral determinants of exercise capacity in both patients with chronic obstructive pulmonary disease (COPD) and chronic heart failure (CHF). We hypothesised that differences in these peripheral determinants of performance between COPD and CHF patients are revealed during small muscle mass exercise, where the cardiorespiratory limitations to exercise are diminished. Methods: Eight patients with moderate to severe COPD, eight patients with CHF (NYHA II), and eight age- and sex-matched controls were studied. We measured leg blood flow (Q̇leg) by Doppler ultrasound during submaximal one-legged knee-extensor exercise (KEE), while sampling arterio-venous variables across the leg. The capillary oxyhaemoglobin dissociation curve was reconstructed from paired femoral arterial-venous oxygen tensions and saturations, which enabled the estimation of O2 parameters at the microvascular level within skeletal muscle, so that skeletal muscle oxygen conductance (DSMO2) could be calculated and adjusted for flow (DSMO2/Q̇leg) to distinguish convective from diffusive oxygen transport. Results: During KEE, Q̇leg increased to a similar extent in CHF (2.0(0.4) L/min) and controls (2.3 (0.3) L/min), but less in COPD patients (1.8 (0.3) L/min) (p<0.03). There was no difference in resting DSMO2 between COPD and CHF and when adjusting for flow, the DSMO2 was higher in both groups compared to controls (COPD: 0.97(0.23) vs. controls 0.63(0.24) mM/kPa, p=0.02; CHF 0.98(0.11) mM/kPa vs. controls, p=0.001). The Q̇-adjusted DSMO2 was not different in COPD and CHF during KEE (COPD: 1.19(0.11) vs. CHF: 1.00(0.18) mM/kPa; p=0.24) but remained higher in COPD vs. controls: 0.87(0.28) mM/kPa (p=0.02), because CHF did not increase Q̇-adjusted DSMO2 (p=0.2) as the other groups. Conclusion: Disease-specific factors may play a role in peripheral exercise limitation in patients with COPD compared with CHF. Thus, low convective O2 transport to contracting muscle seemed to predominate in COPD, whereas muscle diffusive O2 transport was unresponsive in CHF.